x+6=7x+9

Simple and best practice solution for x+6=7x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6=7x+9 equation:


Simplifying
x + 6 = 7x + 9

Reorder the terms:
6 + x = 7x + 9

Reorder the terms:
6 + x = 9 + 7x

Solving
6 + x = 9 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
6 + x + -7x = 9 + 7x + -7x

Combine like terms: x + -7x = -6x
6 + -6x = 9 + 7x + -7x

Combine like terms: 7x + -7x = 0
6 + -6x = 9 + 0
6 + -6x = 9

Add '-6' to each side of the equation.
6 + -6 + -6x = 9 + -6

Combine like terms: 6 + -6 = 0
0 + -6x = 9 + -6
-6x = 9 + -6

Combine like terms: 9 + -6 = 3
-6x = 3

Divide each side by '-6'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| -12X+8=64 | | -0.3+r=4.2 | | -2(-3w+1)-7w=5(w-2)-8 | | 200=2*3.14*X^2+2*3.14*X*6 | | 200=2*(Pi)*X^2+2*(Pi)*X*6 | | -9(v+5)=-7v-37 | | 200=2*pi*X^2+2*pi*X*6 | | 2v-41=-3(v-3) | | -3(x-4)=-8x-13 | | 4x+3(x-6)=17 | | -32=2(v+4)+3v | | 4(y-7)-7y=2 | | -3=-5+2w | | 54x+29(442-x)=17568 | | 7+5(3x-3)=-2(4x-1)+8x | | A=xy*10x | | -3+5=-18 | | 14-6(6X-5)=5(2x-1)-4x | | 5y=-2x+0 | | 13=5u-7 | | -53-2l=-i+20 | | 4x+7=5x-10 | | 2m+6n+7m+9n= | | 3x+y=.14 | | 3x+6-2x=32 | | 20-14x=48 | | 3x+6+-2x=32 | | (8x)2=84 | | 0.40x+0.90(400)=0.50(400+x) | | 10x^2+5xy=0 | | 3x+6-2x=30 | | .25x+1.6=.5x-4.5 |

Equations solver categories